2019
DOI: 10.1111/imm.13095
|View full text |Cite
|
Sign up to set email alerts
|

An agonistic anti‐Toll‐like receptor 4 monoclonal antibody as an effective adjuvant for cancer immunotherapy

Abstract: Summary Immune‐checkpoint blockade antibodies have been approved for the treatment of cancer. However, poorly immunogenic tumours are less responsive to such therapies. Agonistic anti‐Toll‐like receptor 4 (TLR4) monoclonal antibodies (mAbs) activate only cell‐surface TLR4; in contrast, lipopolysaccharide (LPS) activates both TLR4 and intracellular inflammatory caspases. In this study, we investigated the adjuvant activity of an anti‐TLR4 mAb in T‐cell‐mediated antitumour immunity. The anti‐TLR4 mAb induced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
(223 reference statements)
1
10
0
Order By: Relevance
“…Chang and colleagues [ 38 ] demonstrated that the IL-6/JAK/STAT3 signaling pathway drives tumorigenesis and metastasis. The activation of Toll-like receptors (TLRs) leads to a significant increase in IL-6 secretion by bone marrow-derived macrophages [ 39 ]. Pei and colleagues [ 40 ] demonstrated that PC3 human prostate epithelial cells constitutively express TLR4, which plays an important role in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Chang and colleagues [ 38 ] demonstrated that the IL-6/JAK/STAT3 signaling pathway drives tumorigenesis and metastasis. The activation of Toll-like receptors (TLRs) leads to a significant increase in IL-6 secretion by bone marrow-derived macrophages [ 39 ]. Pei and colleagues [ 40 ] demonstrated that PC3 human prostate epithelial cells constitutively express TLR4, which plays an important role in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from tumor cell intrinsic roles of TLR4, its activation has also been shown to mediate antitumorigenic properties through microenvironmental effects. Agonistic antibodies against TLR4 have been shown to enhance the effect of an immune checkpoint blockade with anti PD1 antibodies 32 . In experiments with the chemotherapeutic agent paclitaxel, it has been shown that the therapeutic efficacy was dependent on the expression of TLR4 on macrophages 33 .…”
Section: Discussionmentioning
confidence: 99%
“…It is urgent to find effective adjuvant treatments to improve the efficacy of immune checkpoint inhibitors. Tumors with low numbers of tumorinfiltrating T cells tend to respond poorly to immune checkpoint blockade therapy (Tsukamoto et al, 2019). As mentioned earlier, TLRs play an important role in immune response.…”
Section: Checkpoint Blockade Immunotherapymentioning
confidence: 99%
“…Therapy using ARNAX/TAA can overcome anti-PD-L1 resistance (Takeda et al, 2017). OVA/TLR4 mAb can enhance the anti-tumor effect of anti-PD-1 mAb by activating OVA-specific CD8+ T-cells (Tsukamoto et al, 2019). CIRP is a TLR4 ligand.…”
Section: Checkpoint Blockade Immunotherapymentioning
confidence: 99%